Waist circumference, waist-to-hip ratio cut-off points to predict obesity and metabolic syndrome among student population in skopje, North Macedonia - Zafirova, Biljana; Zhivadinovik Julija; Matveeva, Niki; Trpkovska, Biljana; Chadikovska, Elizabeta; Bojadgieva, Biljana; Dodevski, Ace (Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, 2021)
Abdominal obesity is the most frequently observed component of metabolic syndrome. Any anthropometric measure is only the first step in identifying people at ‘early health risk’. This study aimed to determine a cut-off point of selected anthropometric indicators and to analyze the prevalence of normal weight obesity and abdominal obesity among university students. The study included 839 healthy students aged 18-20 (411 males and 428 females) from the Ss. Cyril and Methodius University in Skopje, R. North Macedonia. The following anthropometric parameters were measured: weight, height, two circumferences (waist WC and hip HC) using a standard protocol. The following indices were taken into consideration: Body Mass Index (BMI), WC and Waist-to-Hip Ratio (WHR). The prevalence of obesity across BMI cut-off points among Macedonian students was 22.22%. In the underweight group, the number of female students was significantly higher (12.61% vs 2.19%), while in the overweight and obesity group a higher percentage of male students was observed (27.5% vs 9.11% and 6.81% vs 1.41%). Prevalence of abdominal obesity according to WC and WHR cut-off among Macedonian students were: female had the prevalence of abdominal obesity (overweight and obese) of 25.47% WC and WHR 43.23%, respectively. Both cut-off points for the males were 34.55% WC and 52.81% WHR. However, the Macedonian cut-off points for WC and WHR showed a higher prevalence of abdominal obesity among males. These results and determination of BMI, WC, WHR cut-off values can be used for the prediction of consequences associated with obesity.
Keywords: BMI; WC; WHR; student population